Improve animal health to reduce livestock emissions: Quantifying an open goal - Kyriazakis, I.; Arndt, Claudia; Aubry, A.; Charlier, J.; Ezenwa, V.O.; Godber, O.F.; Krogh, M.; Mostert, P.F.; Orsel, K.; Robinson, M.W.; Ryan, F.S.; Skuce, P.J.; et al. (Royal Society, 2024)
Greenhouse gas (GHG) emissions from livestock production must be urgently tackled to substantially reduce their contribution to global warming. Simply reducing livestock numbers to this end risks impacting negatively on food security, rural livelihoods and climate change adaptation. We argue that significant mitigation of livestock emissions can be delivered immediately by improving animal health and hence production efficiency, but this route is not prioritized because its benefits, although intuitive, are poorly quantified. Rigorous methodology must be developed to estimate emissions from animal disease and hence achievable benefits from improved health through interventions. If, as expected, climate change is to affect the distribution and severity of health conditions, such quantification becomes of even greater importance. We have therefore developed a framework and identified data sources for robust quantification of the relationship between animal health and greenhouse gas emissions, which could be applied to drive and account for positive action. This will not only help mitigate climate change but at the same time promote cost-effective food production and enhanced animal welfare, a rare win-win in the search for a sustainable planetary future.